2010
DOI: 10.3109/02699206.2010.521612
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic and lexical context of pauses and hesitations in the discourse of Alzheimer patients and healthy elderly subjects

Abstract: Psycholinguistic studies dealing with Alzheimer's disease (AD) commonly consider verbal aspects of language. In this article, we investigated both verbal and non-verbal aspects of speech production in AD. We used pauses and hesitations as markers of planning difficulties and hypothesized that AD patients show different patterns in the process of discourse production. We compared the distribution, the duration and the frequency of speech dysfluencies in the spontaneous discourse of 20 AD patients with 20 age, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 44 publications
7
29
1
9
Order By: Relevance
“…These differences in vocal features were not perceptible to the ear of a clinician most of the time; however, they were detectable by the developed speech analysis algorithm. Our results are in line with the findings from Gayraud et al [42], who showed that patients with AD differ from controls in their process of discourse production, displaying more frequent silent pauses outside the syntactic boundaries, which might be a marker of planning difficulties. Meilan et al [20] found that the increase in voiceless segments in a patient's speech is a sign that explains more than 34% of the variance in scores obtained for a specific language and memory test.…”
Section: Discussionsupporting
confidence: 93%
“…These differences in vocal features were not perceptible to the ear of a clinician most of the time; however, they were detectable by the developed speech analysis algorithm. Our results are in line with the findings from Gayraud et al [42], who showed that patients with AD differ from controls in their process of discourse production, displaying more frequent silent pauses outside the syntactic boundaries, which might be a marker of planning difficulties. Meilan et al [20] found that the increase in voiceless segments in a patient's speech is a sign that explains more than 34% of the variance in scores obtained for a specific language and memory test.…”
Section: Discussionsupporting
confidence: 93%
“…Some authors [1][37] have reported that classical ASR systems exhibit poor performances with elderly voice. These few studies were relevant for their comparison between ageing voice vs. non-ageing voice on ASR performance, but their fields were quite far from our call for help institutions topic of automation commands recognition, and no study was done in French language, except for pathologic voices [14]. In this paper, we present the results of our study related to a system able to detect the call of elderly for emergency when they are in a distress case.…”
Section: Information and Communication Technology (Ict)mentioning
confidence: 92%
“…To the best of our knowledge, very few corpora are related to ageing voices in French [14]. The different available corpora are stems of projects related to the study of French language like the "Corpus de Français Parlé Parisien des années 2000 5 ".…”
Section: State Of the Artmentioning
confidence: 99%
“…En effet, les études utilisant des batteries standardisées pour les patients aphasiques n'ont pas révélé de perturbations phonémiques et articulatoires chez les patients souffrant de la maladie d'Alzheimer (Appell et al, 1982, Murdoch et al, 1987, Rousseaux et al, 2010. Toutefois, les travaux récents portant sur le discours spontané révèlent que la parole des patients Alzheimer est moins fluente que celle des sujets âgés sains, avec plus de ruptures et d'hésitations (Singh et al, 2001, Ash et al, 2004, Hoffmann et al, 2010, Gayraud et al, 2011. De plus, un nombre croissant de recherches rapportent une présentation atypique de la maladie d'Alzheimer (Dubois et al, 2010) qui se caractérise par une détérioration de la capacité langagière, notamment les processus sémantiques et phonologiques, comme un signe d'entrée dans la pathologie (Greene et al, 1996, Croot et al, 2000, Galton et al, 2000, Davies et al, 2005.…”
Section: Aspects Phonétiques Dans Le Vieillissement Normal Et Dans Launclassified